Petak Prioritas Perbaikan Jalur Kereta Api Lintas Rangkasbitung-Tanah Abang Menggunakan Track Quality Index - Leliana, Arinda; Cahyaningrum, Anandita Estyas; Pramudi, Pramudi (JURNAL TEKNIK SIPIL, 2025)
The Track Quality Index is the reading of the gauge to determine the quality of the track, the higher the TQI value, the more severe the level of damage to a track will be. The government's steps to reduce the number of train accidents, especially those caused by derailments, the limited number of gauge trains owned by the government is one of the existing problems. The number of gauge trains owned by the Directorate General of Railways is 4 gauge trains spread across Java Island, Sumatra Island and Sulawesi Island. This causes the identification of damage to the rail road due to a decrease in the quality of traffic that is not optimal. Thus, a more effective measure is needed to predict the value of the Track Quality Index (TQI) of a railroad crossing other than using data read from the operation of a gauge train. This research was conducted as an alternative equation to make it easier to predict valuesTrack Quality Index (TQI), and determine the location of priority repairs to the railroad tracks so that maintenance can be carried out properly, and the safety aspects of the facilities when crossing the railroad are safe. Based on the results of research on the quality of the traffic on the Rangkasbitung-Tanah Abang line, it is included in category II for 20 TQI 35 with good conditions, so that this line can be traversed by trains with speeds of 80-100 km/hour. The Track Quality Index (TQI) score with the highest score is on the Rangkasbitung-Tanah Abang route located on the KM 42+27 to 42+0 road plot with a Track Quality Index (TQI) value of 84.2 which is included in category IV with dangerous conditions. This condition requires very immediate repair of damage to the lift, electricity, and elevation. Then there are 42 other points with category IV which are included in the first priority to be repaired very soon.